Organic micro-nano eutectic crystal with visible light driven continuous directional movement property and preparation method and application thereof

By using the non-covalent weak interaction co-assembly method between electron donor molecules and electron acceptor molecules in light-responsive organic micro-nano actuators, the difficulty in achieving accurate light-controlled actuators in the existing technology is solved. The problem of mechanical force output achieves the effect of continuous directional movement driven by visible light.

CN119350168APending Publication Date: 2025-01-24INST OF CHEM CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411439081.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing photoresponsive organic micro-nano actuators are difficult to achieve precise mechanical force output by light-controlled actuators because their composition is always a mixture of reactants and products and are in a dynamic process of change.

Method used

The organic micro -nano -co -crystal crystals obtained by electron -agent molecules and electronic receptor molecules are assembled, which can be assembled by assembly to achieve light energy into mechanical energy, and continuous directional movement is performed under the visible optical driver.

Benefits of technology

It has realized the conversion of light energy into mechanical energy on a microscopic scale, and has the ability to perform continuous directional movement driven by visible light. The movement speed can be controlled by light intensity, scanning speed and environmental temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350168A_ABST
    Figure CN119350168A_ABST
Patent Text Reader

Abstract

The invention provides an organic micro-nano eutectic crystal with a visible light driven continuous directional movement property and a preparation method and application thereof. The organic micro-nano eutectic crystal disclosed by the invention is obtained by co-assembling electron donor molecules and electron acceptor molecules; the co-assembly is realized through non-covalent bond weak interaction between the electron donor molecules and the electron acceptor molecules. The organic micro-nano eutectic crystal material disclosed by the invention can realize light-driven continuous directional movement on different surfaces under the driving of scanning laser in a specific absorbable wavelength range, and the movement speed of the organic micro-nano eutectic crystal material can be accurately regulated and controlled through the scanning speed of the scanning laser, the intensity of the scanning laser and the environment temperature. The organic micro-nano eutectic crystal disclosed by the invention can be used for converting light energy into mechanical energy on a micro scale to realize a light response material for doing work externally.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photoresponsive organic crystal materials, and in particular to organic micro-nano eutectic crystals with the property of visible light-driven continuous directional motion, and a preparation method and application thereof. Background Art

[0002] The widespread use of machines has saved a lot of manpower and time costs in engineering manufacturing, but the current design and processing level is still insufficient for manufacturing machines with tiny size and nanometer precision. One of the main limitations in manufacturing such machines is the lack of actuators with nanometer-level control accuracy. Traditional macroscopic actuators are difficult to provide precise mechanical force output at the micro-nano level. Therefore, the development of new micro-nano actuators that can achieve micro-nano precision control has become the main challenge at present.

[0003] Photoresponsive organic micro-nano actuators are ideal for overcoming this challenge due to their remote controllability of light, the nanoscale size of molecules, unlimited molecular design potential, and rich synthetic methods. However, photoresponsive organic micro-nano actuators are usually based on the mechanical force generated by chemical reactions of the building block molecules (such as azobenzenes, diarylethenes, helicene molecular motors, etc.). The principle of the photoactuator based on the photochemical reaction mechanism is that the lattice changes inside the crystal after the chemical reaction generate stress, which is amplified by a large number of repeated lattice changes in the crystal to achieve macroscopic mechanical force release. This mechanical response based on photochemical reactions is difficult to use light to precisely control the mechanical movement of organic micro-nano crystals because the composition of organic micro-nano crystals is always a mixture of reactants and products and is in a dynamic change process. Therefore, it is necessary to develop a new type of organic micro-nano crystals that have the property of quickly returning to the initial state after the light-driven mechanical force output, so as to realize the precise mechanical force output of the light-controlled actuator. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0005] An organic micro-nano eutectic crystal is obtained by co-assembling electron donor molecules and electron acceptor molecules; the co-assembly is achieved through weak non-covalent bond interactions between the electron donor molecules and the electron acceptor molecules.

[0006] According to an embodiment of the present invention, the organic micro-nano eutectic crystals include molecular building blocks, and the molecular building blocks are co-assembled by electron donor molecules and electron acceptor molecules, preferably co-assembled by non-covalent weak interactions between electron donor molecules and electron acceptor molecules.

[0007] According to an embodiment of the present invention, the organic micro-nano eutectic crystal is obtained by co-assembling electron donor molecules and electron acceptor molecules in an alternating arrangement.

[0008] According to an embodiment of the present invention, the molar ratio of the electron donor molecule to the electron acceptor molecule is 0.9-1.1:0.9-1.1, preferably 1:1.

[0009] According to an embodiment of the present invention, the electron donor molecule may be selected from at least one of substances having the following structures:

[0010]

[0011] According to an embodiment of the present invention, the electron acceptor molecule may be selected from at least one of substances having the following structures:

[0012]

[0013] According to an embodiment of the present invention, the organic micro-nano eutectic crystal can convert light energy into mechanical energy, and preferably has a continuous directional motion on the surface driven by visible light at a microscopic scale (micrometer level).

[0014] Preferably, the surface is selected from, for example, a dry glass surface, a single crystal silicon surface, a hydrophilic substrate surface or a hydrophobic monolayer substrate surface.

[0015] According to an embodiment of the present invention, when the light intensity of the light energy is higher than the minimum scanning laser intensity threshold (for example, the threshold is 80 μW) for driving crystal motion, the organic micro-nano eutectic crystal has visible light responsive photoinduced motion.

[0016] According to an embodiment of the present invention, the speed regulation of the visible light driven continuous directional motion of the organic micro-nano eutectic crystal can be achieved by controlling the following conditions: the scanning speed of the light energy, the intensity of the light energy, and the ambient temperature. Preferably, the higher the intensity of the light energy, the faster the directional motion speed of the organic micro-nano eutectic crystal.

[0017] According to an embodiment of the present invention, the light energy refers to a laser with a wavelength of 400-800nm, for example, 500nm, 600nm, 700nm; the greater the wavelength of the laser, the faster the directional movement speed of the organic micro-nano eutectic crystal; preferably, the scanning speed of the laser is 1-200μs / pixel, and the higher the scanning speed of the laser, the faster the directional movement speed of the organic micro-nano eutectic crystal.

[0018] According to an embodiment of the present invention, the movement speed of the organic micro-nano eutectic crystals increases with the increase of ambient temperature, and the environment is stably below a temperature that does not destroy the organic micro-nano eutectic crystals, for example, 0°C, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C.

[0019] According to an embodiment of the present invention, the present invention does not specifically limit the size of the organic micro-nano eutectic crystals; the size includes, for example: a length of 1-500μm (for example, 50μm, 100μm, 200μm, 300μm, 400μm), a width of 0.1-10μm (for example, 0.5μm, 1μm, 5μm), and a height of 0.1-10μm (for example, 0.5μm, 1μm, 5μm).

[0020] According to an exemplary embodiment of the present invention, the organic micro-nano eutectic crystal is obtained by co-assembling the electron donor molecule 3,3,5,5-tetramethylbenzidine and the electron acceptor molecule 7,7,8,8-tetracyano-p-benzoquinone dimethane in an alternating arrangement, and the molar ratio of 3,3,5,5-tetramethylbenzidine to 7,7,8,8-tetracyano-p-benzoquinone dimethane is 1:1.

[0021] The present invention also provides a method for preparing the organic micro-nano eutectic crystal, wherein the preparation method is selected from the following method 1 or method 2:

[0022] Method 1: dissolving the electron donor molecule and the electron acceptor molecule in a good solvent, adding a poor solvent to the good solvent to form a mixed solution, and the electron donor molecule and the electron acceptor molecule in the mixed solution are co-assembled to form an organic micro-nano eutectic crystal;

[0023] Method 2: The electron donor molecules and the electron acceptor molecules are dissolved in a good solvent. As the good solvent evaporates, the electron donor molecules and the electron acceptor molecules are co-assembled to form organic micro-nano eutectic crystals.

[0024] According to the embodiment of the present invention, the prepared organic micro-nano eutectic crystals can also be dispersed and washed in a poor solvent.

[0025] According to an embodiment of the present invention, the good solvent is selected from at least one of dichloromethane, chloroform, ethanol, tetrahydrofuran, acetone, acetonitrile and the like.

[0026] According to an embodiment of the present invention, the poor solvent is at least one selected from n-hexane, cyclohexane, petroleum ether, methylcyclohexane, water and the like.

[0027] According to an embodiment of the present invention, in method 1, the volume ratio of the good solvent to the poor solvent is 1:1 to 1:10, for example, 1:5.

[0028] The present invention also provides an application of the organic micro-nano eutectic crystal in the field of light response, preferably used in light-responsive organic micro-nano actuators, such as optical switches for precisely controlled photoactuated external work and microfluidic chip pathways.

[0029] Beneficial effects:

[0030] The present invention adopts different electron donor molecules and electron acceptor molecules that can form electron transfer states, utilizes the difference in solubility in good solvents and poor solvents or uses the volatilization method of good solvents to achieve co-assembly of electron donor molecules and electron acceptor molecules through non-covalent weak interactions, and obtains the organic micro-nano eutectic crystals of the present invention.

[0031] The present invention utilizes electron donor molecules and electron acceptor molecules that can form electron transfer states to form organic micro-nano eutectic crystals through non-covalent bonds. Under the irradiation of light in an absorbable wavelength range, the organic micro-nano eutectic crystals undergo transient lattice elastic deformation and move, thereby achieving nanoscale movement of the organic micro-nano eutectic crystals on a dry surface with adjustable speed and continuous directional movement.

[0032] The organic micro-nano eutectic crystal material of the present invention can realize light-driven continuous directional movement on different surfaces under the drive of a scanning laser within a specific absorbable wavelength range, and its movement speed can be precisely controlled by the scanning speed of the scanning laser, the intensity of the scanning laser and the ambient temperature. The present invention can also achieve the control of the movement speed of the organic micro-nano eutectic crystal by changing the composition of the building blocks of the organic eutectic crystal. Therefore, the organic micro-nano eutectic crystal of the present invention can be used as a light-responsive material that converts light energy into mechanical energy on a microscopic scale to achieve external work. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a SEM image of the organic micro-nano eutectic crystal of Example 1 of the present invention.

[0034] Figure 2 This is the UV-visible absorption spectrum of the organic micro-nano eutectic crystal of Example 1 of the present invention.

[0035] Figure 3 This is the single crystal structure of the organic eutectic crystal of Example 1 of the present invention.

[0036] Figure 4 This is the test result of the directional movement of the organic micro-nano eutectic crystal from right to left in Test Example 3 of the present invention.

[0037] Figure 5These are the test results of the directional movement of the organic micro-nano eutectic crystals on the dry hydrophilic glass surface and the hydrophobic glass surface in Test Example 3 of the present invention.

[0038] Figure 6 This is the test result of the unidirectional movement of the organic micro-nano eutectic crystal in Test Example 3 of the present invention.

[0039] Figure 7 The results of the movement process of the organic micro-nano eutectic crystal of Test Example 3 of the present invention under laser conditions of different wavelengths are compared.

[0040] Figure 8 The results of the directional movement of the organic micro-nano eutectic crystals in Test Example 4 of the present invention under different scanning speed conditions are compared.

[0041] Fig. 9 The results of the directional movement of the organic micro-nano eutectic crystals in Test Example 5 of the present invention under different scanning laser intensities are compared.

[0042] Fig.10 The results of the directional movement of the organic micro-nano eutectic crystals of Test Example 6 of the present invention under different ambient temperature conditions are compared.

[0043] Fig.11 This is the UV-visible absorption spectrum of the organic eutectic crystal of Example 2 of the present invention.

[0044] Fig.12 This is the single crystal structure of the organic eutectic crystal of Example 2 of the present invention.

[0045] Fig.13 This is the test result of the directional movement of the organic micro-nano eutectic crystals in Test Example 8 of the present invention.

[0046] Fig.14 This is the UV-visible absorption spectrum of the organic eutectic crystal of Example 3 of the present invention.

[0047] Fig.15 This is the test result of the directional movement of the organic micro-nano eutectic crystals in Test Example 9 of the present invention. DETAILED DESCRIPTION

[0048] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0049] The raw materials and reagents used in the following examples are all commercially available products: 3,3,5,5-tetramethylbenzidine (Aladdin, 98%), 7,7,8,8-tetracyanobenzoquinodimethane (Tessin, >98%), 3,6-dibromocarbazole (Inotech, 98%), tetrachlorobenzoquinone (Aladdin, 98%), petroleum ether (Concord, analytical grade), n-hexane (Concord, premium grade), dichloromethane (Concord, analytical grade), trichloro(octadecyl)silane (Alfa Aesar, 95%), toluene (Concord, analytical grade), concentrated sulfuric acid (Tianjin Tianzheng, 98%), hydrogen peroxide (Sinopharm, 30% analytical grade), acetone (Concord, analytical grade), and glass (Thermo Fisher).

[0050] Preparation Example

[0051] Preparation of hydrophilic substrate: After cleaning the glass slide with acetone, soak it in a mixed solution of hydrogen peroxide and concentrated sulfuric acid (volume ratio is 1:1 to 3:1) for 2 to 5 hours, and then rinse the soaked glass slide with acetone again before use;

[0052] Preparation of hydrophobic monolayer substrate: Soak a hydrophilic glass slide in a toluene solution of trichloro(octadecyl)silane (volume ratio of 0.1 to 1:100) for 2 to 5 hours, and rinse it with acetone before use.

[0053] Example 1

[0054] Preparation of organic micro-nano eutectic crystals 1:

[0055] (1) 0.9 mg of electron donor molecule (3,3,5,5-tetramethylbenzidine) and 0.8 mg of electron acceptor molecule (7,7,8,8-tetracyanoquinodimethane) were dissolved in 4 mL of dichloromethane, and 30 mL of n-hexane was slowly added. The mixture was allowed to stand to gradually grow a plurality of organic micro-nano eutectic crystals 1 with the property of continuous directional motion driven by visible light. The organic micro-nano eutectic crystals were co-assembled through the weak non-covalent bond interaction between the electron donor molecule and the electron acceptor molecule.

[0056] (2) The organic micro-nano eutectic crystal 1 obtained in step (1) is placed in n-hexane and shaken to disperse and repeatedly washed. The SEM image of the organic micro-nano eutectic crystal 1 is as follows: Figure 1 As shown, from Figure 1 It can be seen that in this embodiment, organic micro-nano eutectic crystals 1 of different sizes are prepared, and the size range is: length is 10-500 μm, width is 0.1-50 μm, and height is 0.1-20 μm.

[0057] The organic micro-nano eutectic crystal obtained in step (2) is placed in an ultrasonic environment, and crushed under the action of ultrasound to obtain crystals of smaller sizes, which are used for the light-driven continuous directional movement of the organic eutectic crystal; after crushing, organic micro-nano eutectic crystals 1 of the following sizes are obtained respectively: 10×0.94μm, 11.59×0.91μm, 10.46×1.14μm, 19.07×1.25μm, 35×3.15μm, 16.88×0.94μm, 9.38×2.19μm, and 40.33×1.97μm.

[0058] Test Example 1

[0059] The suspension of the organic micro-nano eutectic crystal 1 obtained in Example 1 was filtered to obtain a powder of the eutectic crystal 1. The absorption spectrum of the eutectic crystal 1 powder was tested using a Lambda 1050+ UV-visible near-infrared spectrophotometer. The results were as follows: Figure 2 As shown by Figure 2 It can be seen that the absorption range of eutectic crystal 1 covers the visible light range of 400-800nm.

[0060] Test Example 2

[0061] The crystal of about 120 μm×20 μm×8 μm in Example 1 was taken for single crystal structure analysis. Figure 3 The analysis results confirmed that the crystal is a eutectic crystal composed of 3,3,5,5-tetramethylbenzidine and 7,7,8,8-tetracyanoquinodimethane arranged alternately in a molar ratio of 1:1.

[0062] Test Example 3

[0063] The n-hexane suspensions of the organic micro-nano eutectic crystals 1 of different sizes prepared in Example 1 were subjected to the following directional movement test:

[0064] (1) Drop the n-hexane suspension of eutectic crystal 1 on the surface of a glass slide and blow the solvent dry with nitrogen. Then place it under a laser confocal microscope. Select a eutectic crystal with a size of 10×0.94μm to test the crystal's motion behavior. Set the scanning laser wavelength to 635nm, the scanning laser intensity to 77μW, the scanning speed to 4μs / pixel, the image size to 348×76pixel (108×23μm), use a 40x objective lens for observation, and the ambient temperature to 23°C. The observation results are as follows: Figure 4 As shown, it can be seen that the organic micro-nano eutectic crystal 1 can move from right to left on the surface of the dry glass sheet at a speed of 1250-1350 μm / min.

[0065] (2) Drop the n-hexane suspension of eutectic crystal 1 on the surface of a glass slide and blow the solvent dry with nitrogen. Then place it under a laser confocal microscope. Select a eutectic crystal with a size of 11.59×0.91μm to test the movement effect of the eutectic crystal on the hydrophilic surface. Set the scanning laser wavelength to 635nm, the scanning laser intensity to 77μW, the scanning speed to 4μs / pixel, the image size to 348×76pixel (108×23μm), use a 40x objective lens for observation, and the ambient temperature to 23°C. Figure 5 As shown, organic micro-nano eutectic crystals can undergo directional movement from right to left on the dry hydrophilic glass surface.

[0066] (3) Drop the n-hexane suspension of eutectic crystal 1 on the surface of a glass slide and blow the solvent dry with nitrogen. Then place it under a laser confocal microscope. Select a eutectic crystal with a size of 10.46×1.14μm to test the movement effect of the eutectic crystal on the hydrophobic surface. Set the scanning laser wavelength to 635nm, the scanning laser intensity to 77μW, the scanning speed to 4μs / pixel, the image size to 348×76pixel (108×23μm), use a 40x objective lens for observation, and the ambient temperature to 23°C. Figure 5 As shown, organic micro-nano eutectic crystals can undergo directional movement from right to left on the dry hydrophobic glass surface.

[0067] (4) Test of unidirectional directional movement of organic micro-nano eutectic crystal 1: Set the scanning laser wavelength to 635nm, the scanning laser intensity to 105μW, the scanning speed to 4μs / pixel, the image size to 348×76pixel (108×23μm), use a 40x objective lens for observation, the ambient temperature to 23°C, and the size of the organic micro-nano eutectic crystal 1 to 35×3.15μm. Figure 6 As shown, the organic micro-nano eutectic crystal undergoes a directional motion from right to left on the dry glass surface at a speed of 950-1100 μm / min; then, the organic micro-nano eutectic crystal is rotated 180°, and the organic micro-nano eutectic crystal also undergoes a directional motion from right to left at a speed of 950-1100 μm / min, indicating that the movement of the organic micro-nano eutectic crystal 1 is unidirectional.

[0068] (5) Laser test with different wavelengths: The organic micro-nano eutectic crystal 1 with a size of 35×3.15μm was driven by using scanning lasers with different wavelengths including 635, 515, 488, and 405nm (laser intensity: 77μW, scanning speed: 4μs / Pixel) at 23°C. The image size was set to 348×76pixel (108×23μm) and observed using a 40x objective lens. Figure 7The results of the directional movement of the organic micro-nano eutectic crystal 1 after 108s are compared under the drive of scanning lasers of different wavelengths within the absorbable wavelength range. It can be seen that the organic micro-nano eutectic crystal can not only perform continuous directional movement on the dry glass surface, but also that the driving force of lasers of different wavelengths on the organic micro-nano eutectic crystal 1 is different, and the movement speed of the organic micro-nano eutectic crystal will increase with the increase of wavelength.

[0069] Test Example 4

[0070] The n-hexane suspension of eutectic crystal 1 in Example 1 was dripped onto the surface of a glass sheet and the solvent was blown dry with nitrogen gas, then placed under a laser confocal microscope. A eutectic crystal with a size of 16.88×0.94μm was selected to test the effect of laser scanning speed on the crystal movement speed. The scanning laser wavelength was set to 635nm, the scanning laser intensity was set to 77μW, the image size was set to 348×76pixel (108×23μm), and a 40x objective lens was used for observation. The ambient temperature was 23°C. Figure 8 As shown, when the scanning speed is 2μs / pixel, the movement speed of the organic micro-nano eutectic crystal is 5572-5806μm / min. When the laser scanning speed is reduced to 100μs / pixel, its movement speed is reduced to 187-213μm / min, and its continuous directional movement speed is reduced to less than 0.1 times.

[0071] It can be seen that the movement speed of the crystal can be controlled by changing the scanning speed of the laser confocal microscope scanning laser, and the light-driven directional movement speed of the organic micro-nano eutectic crystal will decrease as the scanning laser scanning speed decreases.

[0072] Test Example 5

[0073] The n-hexane suspension of eutectic crystal 1 in Example 1 was dripped onto the surface of a glass sheet and the solvent was blown dry with nitrogen gas, then placed under a laser confocal microscope. A eutectic crystal with a size of 9.38×2.19μm was selected to test the effect of laser power on the crystal movement speed. The scanning laser wavelength was set to 635nm, the scanning speed was 4μs / pixel, the image size was set to 348×76pixel (108×23μm), and a 40x objective lens was used for observation. The ambient temperature was 23°C. Fig. 9 As shown, the organic micro-nano eutectic crystal 1 can be driven to move by a scanning laser higher than 49μW. In the process of gradually increasing the scanning laser intensity from 49μW to 105μW, the movement speed of the crystal gradually increases from 0-6μm / min to 1134-1284μm / min (the continuous directional movement speed increases by more than 150 times). When the intensity of the scanning laser is higher than 105μW and does not destroy the organic micro-nano eutectic crystal, the movement speed of the organic micro-nano eutectic crystal remains relatively stable.

[0074] It can be seen that the movement speed of the crystal can be controlled by changing the intensity of the scanning laser of the laser confocal microscope; the directional movement behavior of organic micro-nano eutectic crystals has a minimum scanning laser intensity threshold that can drive the crystal movement. When the intensity of the scanning laser is higher than the minimum threshold and lower than the light intensity that can destroy the eutectic crystal, the directional movement speed of the crystal will continue to accelerate until it reaches a stable movement speed.

[0075] Test Example 6

[0076] The n-hexane suspension of eutectic crystal 1 in Example 1 was dripped onto the surface of a glass sheet and the solvent was blown dry with nitrogen gas, then placed under a laser confocal microscope. A eutectic crystal with a size of 40.33×1.97μm was selected to test the effect of temperature on the crystal movement speed. The scanning laser wavelength was set to 635nm, the scanning speed was 4μs / pixel, the scanning laser intensity was 75μW, the image size was set to 348×76pixel (215×47μm), and a 20x objective lens was used for observation. Fig.10 As shown, the directional movement speed of the organic micro-nano eutectic crystal 1 at 25°C is 1130-1196 μm / min. When the ambient temperature rises to 105°C, the directional movement speed of the organic micro-nano eutectic crystal gradually increases to 1960-2158 μm / min, and its continuous directional movement speed increases by more than 1 times.

[0077] It can be seen from this that the movement speed of the crystal can be regulated by changing the ambient temperature. Without destroying the crystal, the movement speed of the organic micro-nano eutectic crystal will increase with the increase of ambient temperature.

[0078] Example 2

[0079] Preparation of organic micro-nano eutectic crystals 2:

[0080] 0.5 mg of electron donor molecule (3,3,5,5-tetramethylbenzidine) and 0.511 mg of electron acceptor molecule (tetrachlorobenzoquinone) were dissolved in 1.011 mL of dichloromethane, and the solvent dichloromethane was evaporated by reducing the pressure to obtain organic micro-nano eutectic crystal 2 with the property of continuous directional motion driven by visible light. n-hexane was added to the obtained organic eutectic crystal and shaken to obtain a n-hexane suspension of dispersed organic micro-nano eutectic crystal 2. According to the UV-visible absorption test process of Test Example 1, the UV-visible absorption spectrum of eutectic crystal 2 was obtained, and the results are as follows: Fig.11 As shown by Fig.11 It can be seen that the absorption range of eutectic crystal 2 covers the visible light range of 400-800nm.

[0081] Test Example 7

[0082] The crystal of Example 2 with a size of about 200 μm×50 μm×10 μm was taken for single crystal structure analysis. Fig.12 The analysis results confirmed that the crystals were eutectic crystals composed of 3,3,5,5-tetramethylbenzidine and tetrachlorobenzoquinone arranged alternately in a molar ratio of 1:1.

[0083] Test Case 8

[0084] The n-hexane suspension of eutectic crystal 2 in Example 2 was dripped onto the surface of a glass sheet and the solvent was blown dry with nitrogen gas, then placed under a laser confocal microscope. A eutectic crystal with a size of 8.49×0.66μm was selected to test the motion effect of the eutectic crystal. The scanning laser wavelength was set to 635nm, the scanning laser intensity was 63μW, the scanning speed was 4μs / pixel, the image size was set to 348×76pixel (108×23μm), and a 40x objective lens was used for observation. The ambient temperature was 23°C. The observation results are as follows: Fig.13 As shown, it can be seen that the organic micro-nano eutectic crystal 2 can move from right to left on the surface of the dry glass sheet at a speed of 1600-1900 μm / min.

[0085] Example 3

[0086] Preparation of organic micro-nano eutectic crystals 3:

[0087] Using the same organic eutectic preparation method as in Example 1, 0.32 mg of electron donor molecule (3,6-dibromocarbazole) and 0.20 mg of electron acceptor molecule (7,7,8,8-tetracyanoquinodimethane) were dissolved in 1.2 mL of dichloromethane, 10 mL of petroleum ether was added, and various sizes of organic micro-nano eutectic crystals 3 with visible light driven continuous directional motion properties were rapidly grown by ultrasound. According to the UV-visible absorption test process of Test Example 1, the UV-visible absorption spectrum of eutectic crystal 3 was obtained, and the results are as follows. Fig.14 As shown by Fig.14 It can be seen that the absorption range of eutectic crystal 3 covers the visible light range of 400-800nm.

[0088] Test Example 9

[0089] The petroleum ether suspension of eutectic crystal 3 in Example 3 was dripped onto the surface of a glass sheet and the solvent was blown dry with nitrogen gas, and then placed under a laser confocal microscope. A eutectic crystal with a size of 5.34×0.76μm was taken to test the motion effect of the eutectic crystal. The scanning laser wavelength was set to 635nm, the scanning laser intensity was 77μW, the scanning speed was 4μs / pixel, the image size was set to 348×76pixel (108×23μm), and a 40x objective lens was used for observation. The ambient temperature was 23°C. The observation results are as follows: Fig.15As shown, it can be seen that the organic micro-nano eutectic crystal 3 can move from right to left on the surface of the dry glass sheet at a speed of 1400-1600 μm / min.

[0090] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An organic micro-nano eutectic crystal, characterized in that: The organic micro-nano eutectic crystal is obtained by co-assembling electron donor molecules and electron acceptor molecules; the co-assembly is achieved by the non-covalent weak interaction between the electron donor molecules and the electron acceptor molecules.

2. The organic micro-nano eutectic crystal according to claim 1, characterized in that: The organic micro-nano eutectic crystals include molecular building blocks, and the molecular building blocks are obtained by co-assembly of electron donor molecules and electron acceptor molecules, preferably by co-assembly of weak non-covalent bond interactions between the electron donor molecules and the electron acceptor molecules. Preferably, the organic micro-nano eutectic crystals are obtained by co-assembling electron donor molecules and electron acceptor molecules in an alternating arrangement. Preferably, the molar ratio of the electron donor molecule to the electron acceptor molecule is 0.9-1.1:0.9-1.

1.

3. The organic micro-nano eutectic crystal according to claim 1 or 2, characterized in that: The electron donor molecule is selected from at least one of the substances having the following structures:

4. The organic micro-nano eutectic crystal according to any one of claims 1 to 3, characterized in that: The electron acceptor molecule is selected from at least one of the substances having the following structures:

5. The organic micro-nano eutectic crystal according to any one of claims 1 to 4, characterized in that: The organic micro-nano eutectic crystal converts light energy into mechanical energy, and preferably has continuous directional motion on the surface driven by visible light at a microscopic scale. Preferably, when the light intensity of the light energy is higher than the minimum scanning laser intensity threshold for driving crystal motion, the organic micro-nano eutectic crystal has visible light responsive photoinduced motion.

6. The organic micro-nano eutectic crystal according to any one of claims 1 to 5, characterized in that: The speed regulation of the visible light driven continuous directional motion of the organic micro-nano eutectic crystal is achieved by controlling the following conditions: light energy scanning speed, light energy intensity, and ambient temperature. Preferably, the higher the light energy intensity, the faster the directional motion speed of the organic micro-nano eutectic crystal. Preferably, the light energy refers to laser light with a wavelength of 400-800 nm.

7. The organic micro-nano eutectic crystal according to any one of claims 1 to 6, characterized in that: The movement speed of the organic micro-nano eutectic crystal increases with the increase of the ambient temperature, and the ambient temperature is stably lower than the temperature that does not destroy the organic micro-nano eutectic crystal.

8. The method for preparing the organic micro-nano eutectic crystal according to any one of claims 1 to 7, characterized in that: The preparation method is selected from the following method 1 or method 2: Method 1: dissolving the electron donor molecule and the electron acceptor molecule in a good solvent, adding a poor solvent to the good solvent to form a mixed solution, and the electron donor molecule and the electron acceptor molecule in the mixed solution are co-assembled to form an organic micro-nano eutectic crystal; Method 2: The electron donor molecules and the electron acceptor molecules are dissolved in a good solvent. As the good solvent evaporates, the electron donor molecules and the electron acceptor molecules are co-assembled to form organic micro-nano eutectic crystals.

9. The preparation method according to claim 8, characterized in that: The prepared organic micro-nano eutectic crystals are placed in a poor solvent for dispersion and washing. Preferably, the good solvent is selected from at least one of dichloromethane, chloroform, ethanol, tetrahydrofuran, acetone and acetonitrile. Preferably, the poor solvent is selected from at least one of n-hexane, cyclohexane, petroleum ether, methylcyclohexane and water. Preferably, in method 1, the volume ratio of the good solvent to the poor solvent is 1:1 to 1:

10.

10. Application of the organic micro-nano eutectic crystal according to any one of claims 1 to 7 in the field of photoresponse.

Citation Information

Patent Citations

  • Organic eutectic field effect transistor and preparation method thereof

    CN110350085A

  • Organic eutectic material and preparation method and application thereof

    CN114702496A

  • Full-spectrum organic eutectic material based on tetracyano p-benzoquinone and application of full-spectrum organic eutectic material in water evaporation

    CN116102460A

  • Organic photo-thermal eutectic-based dual-stimulus response color-changing sensor and preparation method thereof

    CN118291117A

  • Optical switching element

    JP1993183175A